An Overview of the Development of Hinduism in Contemporary Indonesia - Rafli Kahfi; Darwis Mustakim; Fadillah Utami; Indri Apriliani (Sufiya Journal of Islamic Studies, 2023)
In South Asia, Hinduism in Indonesia is the predominant religion, particularly in India and Nepal, home to various traditions. Western academics consider Hinduism a synthesis or fusion of several Indian traditions and cultures with many different roots and no central founder. Brahmanism, an old Vedic religion, is one of its foundations. Through trade, the religions of the River Valley civilization conveyed this message to Indonesia. What is its development history, and how are Hindu teachings received in Indonesia? The technique is literature study, which uses sources from books and journals. The goal is to learn more about Hinduism’s history and philosophical teachings in Indonesia. Hinduism was made famous in the 19th century as a single-world religious tradition.